Constitucionalizar el orden fiscal en Nueva España: de la Ordenanza de Intendentes a la Constitución de Cádiz (1786-1814) - Sánchez Santiró, Ernest (El Colegio de México, A.C., 2015)
This article is centered on two issues. The first is the study of the Spanish Crown’s constitutionalization initiatives in New Spain in the context of a corporate legal tradition stepped in anthropomorphic analogies. This phenomenon includes the institutional reconfiguration of the Spanish Crown between 1781 and 1793, one of the key aspects of the Bourbon Reforms in New Spain. In its second section, the article analyzes the challenges posed by the Spanish Constitution of 1812 on the nascent treasury of New Spain, then under the strain of a bloody civil war that prevented its institutional development. This will show the diversity of political and fiscal culture in New Spain in terms of the meanings and scopes that can be ascribed to the constitutionalization process, as well as its differing impact on the government, the management of public funds (royal and public/national, depending on the circumstances) and the tax system.